EFEKTIVITAS BIOURIN DAN EKSTRAK TANAMAN TERHADAP PERTUMBUHAN JAGUNG PULUT (Zea mays linneaus) SERTA MENEKAN SERANGAN SPODOPTERA LITURA DENGAN SISTEM ORGANIK - malik abd malik ash shiddieqy; Sylvia Sjam; Abd. Haris Bahrun (Jurnal Ecosolum, 2021)
Abstract Fulfilment of nutrients in the land must be cultivated by increasing the physical and biological properties of the soil so that the presence of nutrients in the ground will be more maintained. The application of technology often used in land use efforts is mostly only focused on chemical fertilization activities. One alternative to reduce the use of chemical fertilizers is to use liquid organic fertilizer (POC) in thitonia and calotropis plant extracts and cow urine. This study aims to obtain a combination of plant extracts that can increase the growth and yield of maize plants and the best blend of biourin and plant extracts in suppressing pests and diseases in maize. The research was carried out on the land of the Faculty of Agriculture, Hasanuddin University (Eksfarm), Makassar City, South Sulawesi, from September to December 2019. The research was arranged using a split-plot design with the first factor as the main plot. The application consisted of 4 levels namely without spraying (K), a combination of bio urine, tithonia extract, calotropis extract, pineapple MOL (B1), bio urine, tithonia extract, calotropis extract (B2) and bio urine (B3) with each application dose of 40 ml/1 liter of water. The second factor as a sub-plot was the spraying interval at the age of 14 DAS which consisted of 3 levels, namely without application, once a week, once in two weeks. The results showed that the application of biourin could increase the growth rate and yield of corn plants. The combination of biourin with plant extracts had a significant effect on the level of pest attack that attacked the leaves and cobs of corn plants and the best interaction between the intervals of application of biourin in increasing the productivity of spraying plants per two weeks.     Keywords: Biourine, Spodoptera litura, Tithonia, Calotropis, Pest attack rate